KUALITAS ESTRUS PADA SAPI PERANAKAN ONGOLE DAN SAPI CROSSBREEDSIMMENTAL â PERANAKAN ONGOLEDI DAERAH ISTIMEWA YOGYAKARTA - , AGUS SUPRIYANTO; , drh. Sri Gustari M.P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The population of crossbreed cattle in Yogyakarta increased sharply, however, some reports a degradation in reproductive performance of crossbreed cattle. Percentage of artificial insemination pregnancy outcomes in Yogyakarta decreased from time to time. One of the factors that influence the success of mating is the quality of estrus. The study aims to determine the quality of estrus in cattle in Daerah Istimewa Yogyakarta. This research conducted with beef cattle, 7 PO and 7 SimPO in Daerah Istimewa Yogyakarta. The criteria of beef cattle was: adult, healthy, regular estrous cycles, and clear estrus symptoms. The beef cattle was observed for length of estrous cycle, length of estrus period, changes in the vulva, cervical fluid production and uterine tension. The results of the research was scored and processed by ANOVA. The results showed that the estrous cycle length in PO was 20.43±1.13 days and SimPO had an average 22.86±0.38 days. The length of estrus periode in PO had an average of 23.71±2.93 hours and SimPO 70.29±4.54 hours. The changes in vulva has a mean in PO 2,43±0,79 and SimPO 2,71±0,49. The intensity of bovine cervical mucus has a mean of PO 2,28±0,95 and SimPO 1,57±0,79. The uterine tension was PO 2,71±0,76 and SimPO 2,57±0,79. The conclusion of this research was the length of the estrous cycle and long periods of estrus in cattle Simpo and PO had significant differences (P < 0.05). The other parameters such as: changes in the vulva, mucus intensity and tension of the uterus in cows and Simpo PO has no significant difference (P > 0.05).